European space agency's hibernation (torpor) strategy for deep space missions: Linking biology to engineering. (December 2021) - Choukér, Alexander; Ngo-Anh, Thu Jennifer; Biesbroek, Robin; Heldmaier, Gerhard; Heppener, Marc; Bereiter-Hahn, Jürgen
Highlights: Travel to outer space and leaving the Earth's exposome imposes extreme physical and mental stresses to the human organism. New insights into the neuronal control of torpor and into the biology of assumed human torpor reducing metabolism as related to gender. Torpor of the crew will reduce the payload (i.e. oxygen, food and water) and requires AI-assisted monitoring of crew and space craft. Reducing the metabolic rate will become a game changer of human space flight and will revolutionize the field of medicine. Abstract: Long-duration space missions to Mars will impose extreme stresses of physical and psychological nature on the crew, as well as significant logistical and technical challenges for life support and transportation. Main challenges include optimising overall mass and maintaining crew physical and mental health. These key scopes have been taken up as the baseline for a study by the European Space Agency (ESA) using its Concurrent Design Facility (CDF). It focussed on the biology of hibernation in reducing metabolism and hence stress, and its links to the infrastructure and life support. We concluded that torpor of crew members can reduce the payload with respect to oxygen, food and water but will require monitoring and artificial intelligence (AI) assisted monitoring of the crew. These studies additionally offer new potential applications for patient care on Earth. Keywords: Space flight, concurrent design facility, metabolic reduction